(untitled) (Indonesian Anti Corruption Studies, 2025)
Blockchain technology offers potential for enhancing transparency and accountability in governance by providing immutable and decentralized record-keeping. This paper conducts a feasibility study on implementing blockchain solutions in Indonesia’s public sector, focusing on anti-corruption applications such as land registration, public procurement, and financial transactions. Using a multidisciplinary approach involving technical assessment, stakeholder interviews, and policy analysis, the study evaluates the opportunities and constraints posed by Indonesia’s technological infrastructure, regulatory environment, and institutional capacity. Findings suggest that while blockchain could reduce corruption risks by improving traceability and reducing intermediaries, challenges related to scalability, legal recognition, and digital literacy must be addressed. The paper recommends a phased implementation combined with pilot projects and regulatory reforms. This research contributes to the growing global literature on blockchain in governance, offering practical insights for policymakers and technologists in similar developing country contexts.